Manganese toxicity impairs soil nitrification and sugarcane nitrogen utilization by inhibiting rhizosphere ammonia-oxidizing microorganisms - Zhu, Hanyu; Pan, Junchen; Qin, Yuqi; Wei, Yanyan; Li, Xiaofeng; Yang, Shu; Chen, Baoshan; Zhong, Taolian; Zhang, Tong; Tang, Xinlian (Frontiers in Plant Science, 2025)
IntroductionSugarcane (Saccharum spp.) is an economically important crop cultivated primarily for sugar and bioethanol production. In southern China, sugarcane grown in acidic soils often exhibits severe leaf chlorosis owing to excessive soil manganese (Mn) levels. However, the mechanisms by which Mn toxicity disrupts soil nitrogen (N) cycling, particularly the roles of ammonia-oxidizing bacteria (AOB) and archaea (AOA) in regulating nitrification and N availability in sugarcane, remain unexplored.MethodsTo address this gap, we conducted laboratory soil incubation experiments and greenhouse pot trials using four treatments consisting of combinations of two N levels (N1:0.14 g·kg-1; N2:0.28 g·kg-1) and two Mn levels (−Mn: 0 mg·kg-1; +Mn: 328 mg·kg-1, simulated using anhydrous Mn sulfate), along with a blank control (CK). Key measurements included rhizosphere soil physicochemical properties, AOB/AOA community structure, nitrification potential, and sugarcane N uptake efficiency.ResultsResults showed that Mn toxicity significantly reduced soil pH and nitrification potential by 75.9–78.0% compared to non-Mn treatments, and AOB amoA gene abundance by 44.9–46.5%, while altering AOB/AOA community composition. Redundancy analysis (RDA) identified soil organic carbon, total nitrogen, and ammonium nitrogen as the primary drivers of AOB community shifts, whereas exchangeable Mn, ammonium nitrogen, and pH dominated AOA community changes. Correlation analysis confirmed that nitrification potential and AOB amoA abundance were strongly positively linked to sugarcane N accumulation and uptake efficiency, which decreased by 47.3–53.4% under Mn toxicity due to reduced nitrate availability.DiscussionThese findings indicate that Mn toxicity impairs sugarcane N utilization by disrupting ammonia-oxidizing microbial communities and suppressing nitrification, thereby providing insights for optimizing N management strategies in Mn-contaminated acidic soils.